2019
DOI: 10.3390/su11072042
|View full text |Cite
|
Sign up to set email alerts
|

Prioritizing Green Spaces for Biodiversity Conservation in Beijing Based on Habitat Network Connectivity

Abstract: Rapid urbanization results in changes in land use, biogeochemical cycles, climate, hydrosystems, and biodiversity. Policy-makers have formulated ecological protection measures to facilitate sustainable development. However, traditional conservation planning mainly focuses on protecting specific green spaces, with limited consideration of the connectivity among green spaces from a habitat network perspective. Using citizen science data and occupancy modelling, we predicted habitat suitability, built habitat net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 61 publications
0
6
0
1
Order By: Relevance
“…Previous urban water system planning has been largely focused on meeting hydrological functions such as water supply and flood control [99,100], and most studies on waterbird protection have focused on areas such as nature reserves, coastal wetland landscapes [101], or more rural landscapes [102]. One exception is a study of Beijing, China, that examined habitat suitability and connectivity for the mallard duck (along with two other bird species; [80]), although only a single time period was examined. Our paper provides a novel contribution by exploring urban waterbird protection from the perspective of changes in the connectivity of urban water bodies over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous urban water system planning has been largely focused on meeting hydrological functions such as water supply and flood control [99,100], and most studies on waterbird protection have focused on areas such as nature reserves, coastal wetland landscapes [101], or more rural landscapes [102]. One exception is a study of Beijing, China, that examined habitat suitability and connectivity for the mallard duck (along with two other bird species; [80]), although only a single time period was examined. Our paper provides a novel contribution by exploring urban waterbird protection from the perspective of changes in the connectivity of urban water bodies over time.…”
Section: Discussionmentioning
confidence: 99%
“…Among waterfowl, one of the most well-studied species is the mallard (Anas platyrhynchos), a duck with generalist feeding habits that breeds in a wide variety of habitats and has broad distribution around the world [76][77][78][79]. This species has been shown to use small urban waterbodies [80] and was observed at many Zhengzhou waterbodies during the wetland resource survey described above; thus we used published mallard-related data to parameterize our connectivity models. Research has shown that the mallard's average flight distance is 0.4 km [81], so we assumed that many ducks would travel this distance in a single flight event.…”
Section: Evaluating Landscape Connectivitymentioning
confidence: 99%
“…UGS also have an important ecological role (Li, H. et al 2015), as they contribute to biodiversity preservation by providing habitats for great number of plants and animals (Threlfall, C.G. et al 2017;Lv, Z. et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, scholars of various research fields have discussed the structure and function of the ecological network [3], as well as its construction and assessment [4,5]. In addition, they have also conducted a great deal of research about biodiversity protection [6,7], natural reserve design [8], optimization and assessment of urban (regional) landscape [9,10], landscape planning and design [11,12], forest management [13], land use planning and assessment [14], and ESP [1,15], etc. The research involving ecological networks and ecological security can be mainly divided into following three types: (1) improving the spatial structure of ecosystem; (2) protecting ecological functions and processes (like the habitat reconstruction of crucial species); (3) coupling ecosystem services (like ecology, entertainment and aesthetics).…”
Section: Introductionmentioning
confidence: 99%